Influence of water column stratification and mixing patterns on the fate of methane produced in deep sediments of a small eutrophic lake. (11th April 2019) - Vachon, Dominic; Langenegger, Timon; Donis, Daphne; McGinnis, Daniel F.
Abstract: Methane (CH4 ), a potent greenhouse gas, is produced in and emitted from lakes at globally significant rates. The drivers controlling the proportion of produced CH4 that will reach the atmosphere, however, are still not well understood. We sampled a small eutrophic lake (Soppensee, Switzerland) in 2016–2017 for CH4 concentrations profiles and emissions, combined with water column hydrodynamics to investigate the fate of CH4 produced in hypolimnetic sediments. Using a mass balance approach for the periods between April and October of both years, net CH4 production rates in hypolimnetic sediments ranged between 11.4 and 17.7 mmol m −2 d −1, of which 66–88% was stored in the hypolimnion, 13–27% was diffused to the epilimnion, and 6–7% left the sediments via ebullition. Combining these results with a process‐based model we show that water column turbulent diffusivity ( K z ) had a major influence on the fate of produced CH4 in the sediments, where higher K z values potentially lead to greater proportion being oxidized and lower K z lead to a greater proportion being stored. During fall when the water column mixes, we found that a greater proportion of stored CH4 is emitted if the lake mixes rapidly, whereas a greater proportion will be oxidized if the water column mixes more gradually. This work highlights the central role of lake hydrodynamics in regulating CH4 dynamics and further suggests the potential for CH4 production and emissions to be sensitive to climate‐driven alterations in lake mixing regimes and stratification.